2017
DOI: 10.1515/ngoe-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning Usage and Preferences of Vocational Secondary School Students: The cases of Austria, the Czech Republic, and Germany

Abstract: The purpose of this paper is to determine the current status of mobile device usage and mobile learning adoption in vocational education and training (VET) secondary schools in three European Union countries (Austria, the Czech Republic, and Germany). The research focused on exploring students' mobile device usage habits, their attitudes toward education in the context of mobile application support, and preferences regarding mobile learning features. The research confirmed a high level of mobile device usage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
3
15
0
3
Order By: Relevance
“…practitioner 9) to educate, collaborate and communicate with athletes across various environments, contexts and times of day. This finding is consistent with trends in pedagogy, again highlighting sports nutrition is no different to global trends, as social media and online platforms continue to establish a supporting role for itself in the education system (Biloš, Turkalj, and Kelić, 2017;Brooks, 2016;Cheston, Flickinger, and Chisolm, 2013;Moran, Seaman, and Tinti-Kane, 2011). Pascarella and Terenzini (2005) investigated the impacts of incorporating these platforms into the teaching activities of their university faculties and found that the most effective faculty members used social media with their students as a platform for active learning as well as to engage students in real-time, with minimal hindrances.…”
Section: Mobile Learning Nudging and Visual Learningsupporting
confidence: 55%
See 1 more Smart Citation
“…practitioner 9) to educate, collaborate and communicate with athletes across various environments, contexts and times of day. This finding is consistent with trends in pedagogy, again highlighting sports nutrition is no different to global trends, as social media and online platforms continue to establish a supporting role for itself in the education system (Biloš, Turkalj, and Kelić, 2017;Brooks, 2016;Cheston, Flickinger, and Chisolm, 2013;Moran, Seaman, and Tinti-Kane, 2011). Pascarella and Terenzini (2005) investigated the impacts of incorporating these platforms into the teaching activities of their university faculties and found that the most effective faculty members used social media with their students as a platform for active learning as well as to engage students in real-time, with minimal hindrances.…”
Section: Mobile Learning Nudging and Visual Learningsupporting
confidence: 55%
“…Maloney, Moss and Ilic (2014) explored students' perspectives of these platforms use in education, demonstrating that students felt it was appropriate and would benefit their learning by facilitating peer collaboration, enhanced communication and complementary learning. Biloš et al (2017) states that this augmentation of practice through mobile devices and applications can enrich traditional learning. Perhaps this is because mobile learning facilitates communication in a highly situated and contextualized manner, enabling learning to take place in the context in which it is applied, as proposed by the Situated Learning Theory (Lave and Wenger, 1991).…”
Section: Mobile Learning Nudging and Visual Learningmentioning
confidence: 99%
“…Mobile technologies have started to make compelling contributions to mobile learning within training institutes in developing countries, such as Iran. Similar to other studies by Kumar et al (10) and Bilos et al (11), learners stated mostly positive attitudes towards use of mobile devices for various activities, including mobile learning. This situation suggests a vast space for improvement of the classroom experience with mobile devices, such as smart phones.…”
Section: Discussionsupporting
confidence: 87%
“…Allowing for greater collaboration among students, creation of knowledge and skills, and better interaction and communication between teacher and student [14]. Despite the advantages identified in the literature and presented here, however, there are always contrasting scenarios in all contexts, including m_learning [15], such as student performance, known to be "effective", can be disappointing or can even adversely affect students if they do not have a proper treatment Chu [16].…”
Section: M_learningmentioning
confidence: 99%